Evaluation of age-related changes in the vitreous using magnetic resonance imaging - Kuzan, Beyza Nur; Kuzan, Taha Yusuf; Buğdaycı, Onur (The European Research Journal, 2023)
Objectives: Age-related liquefaction of vitreous humor may result in posterior vitreous detachment, retinal tear, and detachment. The purpose of this study is to determine the normative values of age-related changes in the vitreous in the normal population using different MRI sequences. Methods: A total of 180 eyes of 90 healthy cases were enrolled in this retrospective study. Patients were divided into nine groups according to age, and each group was of equal size with 10 patients(5 male and 5 female). The T1, T2, standardized T1, standardized T2 signals and ADC values determined for each vitreous humor of each eye. MRI parameters of the vitreous were compared within and between age groups. Results: No difference was detected within the decadic age groups for mean T1W for the right and left (p = 0.912 and p = 0.903, respectively), T2W for the right and left (p = 0.966 and p = 0.983, respectively), standardized T2W for the right and left (p = 0.915 and p = 0.899, respectively), and ADC for right and left values (p = 0.622 and p = 0.524, respectively). A significant difference was found between decadic age groups in terms of the standardized T1W values for right and left (p < 0.001 and p < 0.001, respectively). Standardized T1W values of vitreous fluid show a moderate degree of correlation with age for the right (r=0.514, p < 0.001) and left eyes (r=0.534, p < 0.001). Conclusions: This study provides comprehensive normative data on the different MRI signal properties of the human vitreous and its change with age. Using MRI, especially with standardized T1 measurements, age-related changes in the vitreous humor can be revealed non-invasively.